Evaluation of the effectiveness of coenzyme Q10 gel in management of patients with chronic periodontitis (I intra group comparison) - Salih, Taif M; Mahmood, Maha S (Journal of Baghdad College of Dentistry, 2015)
Background: Periodontal pathogens can induce free radicals over-formation and thus may cause collagen and periodontal destruction. Anti-oxidants are used as supplements to counteract the over production of free radicals in periodontal disease, that can reduce of collagen destruction. Coenzyme Q10 serves as an endogenous antioxidant, regenerates other antioxidants, stimulates cell growth, and inhibits cell death. Because it is an antioxidant, coenzyme Q10 has received much research attention associated with periodontal diseases. Perio Q gel may possibly be effective as a topical agent and as an adjunct to scaling& root planing in treatment of gingivitis and chronic periodontitis. Aim of study:Determine the periodontal health status in a follow up study for 6 weeks of a group of patients with chronic periodontitis by measuring clinical periodontal parameters, which included (Plaque index, Gingival index, Bleeding on Probing, Probing Pocket Depth and Relative Attachment Level) and to evaluate the effect of intra pocket application of perio Q gel (coenzyme Q10) alone & as adjunct to scaling,& root planing on the periodontal clinical parameters in the management of patients with chronic periodontitis. Materials and methods: A total of 323 sites with pocket depth (5-8) mm in patients with chronic periodontitis were randomly divided in three groups. The Gel group, 111 sites were treated with intra-pocket application of Perio Q gel alone. In the Combination group, 106 sites were treated with scaling and root planning (SRP) plus intra- pocket application of Perio Q gel, in Scaling and root planing group, 106 sites were treated with scaling and root planing alone. Clinical periodontal parameters such as Plaque index (PI), Gingival index (GI), Bleeding on probing (BOP), Probing pocket depth (PPD), Relative attachment level (RAL) were assessed at first visit, 3weeks and 6weeks. Results: on intra-group analysis, all groups showed highly significant reduction in PI, GI, BOP, PPD and RAL among the three visits .On inter-group analysis, the results showed significant reduction in the clinical parameters PPD and RAL of combination group in comparison to SRP group. Conclusion: The results of the research were encouraging and suggested the possibility to use the gel as a sole agent to support standard treatment procedures in periodontitis. The clinical parameters significantly improved in the phase of periodontal treatment, indicating that CoQ10 opens new treatment options by improving the host response to disease activity.